2017
DOI: 10.1097/imi.0000000000000387
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Navigational Bronchoscopy Reduces the Time Required for Localization and Resection of Lung Nodules

Abstract: Objective The aims of the study were to evaluate electromagnetic navigational bronchoscopy (ENB) and computed tomography–guided placement as localization techniques for minimally invasive resection of small pulmonary nodules and determine whether electromagnetic navigational bronchoscopy is a safer and more effective method than computed tomography–guided localization. Methods We performed a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
1
5
1
Order By: Relevance
“…The pathology diagnosis of malignancy was obtained before VATS in 56% of the patients, thereby preventing the wedge resection otherwise necessary for this diagnosis. On one hand, this proportion is higher than that reported by W. Bolton perprocedural decisional algorithm similar to ours with a transbronchial needle aspiration yielding the peroperative pathology diagnosis in approximately one fourth of the patients [9,20]. On the other hand, this proportion is lower than the two thirds reported in two systematic reviews addressing the performance of ENB-guided forceps biopsy of peripheral lung nodules of any size [21,22].…”
Section: Discussioncontrasting
confidence: 50%
“…The pathology diagnosis of malignancy was obtained before VATS in 56% of the patients, thereby preventing the wedge resection otherwise necessary for this diagnosis. On one hand, this proportion is higher than that reported by W. Bolton perprocedural decisional algorithm similar to ours with a transbronchial needle aspiration yielding the peroperative pathology diagnosis in approximately one fourth of the patients [9,20]. On the other hand, this proportion is lower than the two thirds reported in two systematic reviews addressing the performance of ENB-guided forceps biopsy of peripheral lung nodules of any size [21,22].…”
Section: Discussioncontrasting
confidence: 50%
“…[19,20] Pooled pneumothorax rate in studies using ENB-guided dye marking was 0% and none of the studies reported bronchopulmonary hemorrhage. [68,21,22] We also did not experience bronchial hemorrhage nor pneumothorax in 29 dye injections, and ENB procedure did not compromise subsequent thoracoscopic surgery. If any, localization followed immediately by surgery could mitigates adverse effects of potential complications.…”
Section: Discussionmentioning
confidence: 86%
“…The process and personnel for the transportation of the patient from localization unit to the operation room are not necessary in intraoperative ENB-guided dye marking. Bolton et al [21] reported that ENB-guided localization significantly reduced the waiting time compared with CT-guided localization (27 vs 189 minutes, P = .001).…”
Section: Discussionmentioning
confidence: 99%
“…Injection of lipiodol in addition to the ICG dye allows confirmation of the successful localization as lipiodol could be viewed by fluoroscopy or CT scanning. Compared with CT‐guided localization techniques, there was a less incidence of procedure‐related complications including pulmonary haemorrhage, pneumothorax, haemothorax, haemoptysis and pleural reactions 1–4 . It is important to note that bronchoscopy navigation localization still has limitations in localising those small and centrally located lesions.…”
Section: Discussionmentioning
confidence: 99%
“…niques, there was a less incidence of procedure-related complications including pulmonary haemorrhage, pneumothorax, haemothorax, haemoptysis and pleural reactions. [1][2][3][4] It is important to note that bronchoscopy navigation localization still has limitations in localising those small and centrally located lesions. These lesions may not be visible under the firefly mode of the robotic system even after the injection of ICG.…”
Section: Casementioning
confidence: 99%